2014
DOI: 10.1007/978-3-319-14358-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Towards Principles of Large-Scale Agile Development

Abstract: Abstract. Large projects are increasingly adopting agile development practices, and this raises new challenges for research. The workshop on principles of large-scale agile development focused on central topics in large-scale: the role of architecture, inter-team coordination, portfolio management and scaling agile practices. We propose eight principles for large-scale agile development, and present a revised research agenda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 19 publications
(23 reference statements)
1
92
0
4
Order By: Relevance
“…The largest numbers were 300 people across 3 sites ( Moore and Spens, 2008 ). Participants of the XP2014 large-scale agile workshop gave very varying definitions for large-scale agile development ( Dingsøyr and Moe, 2014 ), showing that what is seen as large-scale depends very much on the context and the person defining it.…”
Section: Definition Of Large-scale Agilementioning
confidence: 99%
See 1 more Smart Citation
“…The largest numbers were 300 people across 3 sites ( Moore and Spens, 2008 ). Participants of the XP2014 large-scale agile workshop gave very varying definitions for large-scale agile development ( Dingsøyr and Moe, 2014 ), showing that what is seen as large-scale depends very much on the context and the person defining it.…”
Section: Definition Of Large-scale Agilementioning
confidence: 99%
“…In addition, large scale may cause users and other stakeholders to become distant from the development teams. Despite these known problems related to large-scale agile, there is an industry trend towards adopting agile methodologies in-the-large ( VersionOne, Inc, 2016;Paasivaara et al, 2013Paasivaara et al, , 2014Dingsøyr and Moe, 2014 ). * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review revealed several papers on large scale agile [7,11,12], but none discussing the scalability of retrospectives.…”
Section: Large Scale Developmentmentioning
confidence: 99%
“…A key change from small-to large-scale is that work across boundaries becomes at least as important as work within teams. The topic of inter-team coordination, which has also been included in the research agenda on large-scale agile development [2], is critical in large projects and development programmes.…”
Section: Introductionmentioning
confidence: 99%